2020
DOI: 10.1051/e3sconf/202014501039
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the mechanisms of Hibiscus sabdariffa L. on hypertension

Abstract: As a traditional edible beverage and medicinal application for high-pressure blood treatment with no side effects, Hibiscus sabdariffa L. (HS) has high prospect to be nutraceuticals as diet additive for anti-hypertension. The anti-hypertension effect of HS has also been scientific validated recently especially in diabetic patient and post-partum mothers. In this paper, we reviewed up-to-date mechanisms found for the anti-hypertensive effect of HS extracts. Those included the inhibition of angiotensin-convertin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The application of this plant in traditional medicine has been supported by previous scientific research for the treatment of hypertension (Al Disi et al, 2016;Al-anbaki et al, 2019;Herrera-Arellano et al, 2016;Liu et al, 2020), inflammation (Garbi et al, 2017), type-2 diabetes (Adeyemi & Adewole, 2019;Ndarubu et al, 2019). In addition, scientific evidence has also shown that it possesses hepatoprotective (Bhavana et al, 2017), nephroprotective (Al-Qahtani et al, 2017;Anwar Ibrahim & Noman Albadani, 2014), as well as cancer preventive activities (Fithrotunnisa et al, 2020;Malacrida et al, 2016& Su et al, 2018.…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 84%
“…The application of this plant in traditional medicine has been supported by previous scientific research for the treatment of hypertension (Al Disi et al, 2016;Al-anbaki et al, 2019;Herrera-Arellano et al, 2016;Liu et al, 2020), inflammation (Garbi et al, 2017), type-2 diabetes (Adeyemi & Adewole, 2019;Ndarubu et al, 2019). In addition, scientific evidence has also shown that it possesses hepatoprotective (Bhavana et al, 2017), nephroprotective (Al-Qahtani et al, 2017;Anwar Ibrahim & Noman Albadani, 2014), as well as cancer preventive activities (Fithrotunnisa et al, 2020;Malacrida et al, 2016& Su et al, 2018.…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 84%
“…1 Several drugs used for treating hypertension belong to the angiotensin-converting enzyme (ACE) inhibitor class, which work by inhibiting the conversion of angiotensin-I to angiotensin-II, a vasopressor that triggers an increase in blood pressure. 2,3 However, antihypertensive drugs have limitations because they must be adjusted to the patient's health condition, especially those with contraindications. 1 In addition, the long-term use of synthetic drugs can cause undesired side effects, such as hypersensitivity reactions, itching, hypotension, and upper respiratory tract infections.…”
Section: Introductionmentioning
confidence: 99%
“…32 One of the physiological properties of the phytochemicals contained in H. sabdariffa and C. sativus is their ability to inhibit ACE. 2,7,33 In several studies, observations of ACE-inhibitory activity were carried out by initially extracting the plants in the form of decoction/infusion, 22,23 but the doses used were still varied, so the therapeutic effects observed were still inconsistent. 34 Furthermore, no previous study has directly measured the ACE inhibitory activities of H. sabdariffa and C. sativus from their infusions.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological studies have demonstrated that the anthocyanins from roselle, specially cyanidin‐3‐sambubioside and delphinidin‐3‐sambubioside, are involved in the majority of the blood pressure‐lowering mechanisms (Hopkins et al, 2013; Liu et al, 2020). The beneficial effect of roselle extracts on blood pressure reduction in normotensives and hypertensives has been well documented in both human and animal studies (Herrera‐Arellano et al, 2007; Hopkins et al, 2013; Inuwa et al, 2012; McKay et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological studies have demonstrated that the anthocyanins from roselle, specially cyanidin-3-sambubioside and delphinidin-3-sambubioside, are involved in the majority of the blood pressure-lowering mechanisms (Hopkins et al, 2013;Liu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%